Kangaroo mother care: using formative research to design an acceptable community intervention - Sarmila Mazumder; Ravi Prakash Upadhyay; Zelee Hill; Sunita Taneja; Brinda Dube; Jasmine Kaur; Medha Shekhar; Runa Ghosh; Shruti Bisht; Jose Carlos Martines; Rajiv Bahl; Halvor Sommerfelt; et al. (BMC, 2018)
Abstract Background Low and middle income countries (LMICs), including India, contribute to a major proportion of low birth weight (LBW) infants globally. These infants require special care. Kangaroo Mother Care (KMC) in hospitals is a cost effective and efficacious intervention. In institutional deliveries, the duration of facility stay is often short. In LMICs, a substantial proportion of deliveries still occur at home and access to health care services is limited. In these circumstances, a pragmatic choice may be to initiate KMC at home for LBW babies. However, evidence is lacking on benefits of community-initiated KMC (cKMC). Promoting KMC at home without an understanding of its acceptability may lead to limited success. Methods We conducted formative research to assess the feasibility, acceptability and adoption of cKMC with the aim of designing an intervention package for a randomised controlled trial in LBW infants in Haryana, India. Qualitative methods included 40 in-depth interviews with recently delivered women and 6 focus group discussions, two each with fathers and grandfathers, grandmothers, and community health workers. A prototype intervention package to promote cKMC was developed and tested in 28 mother-infant pairs (of them, one mother had twins), using Household (HH) trials. Results We found that most mothers in the community recognized that babies born small required special care. In spite of not being aware of the practice of KMC, respondents felt that creating awareness of KMC benefits will promote practice. They expressed concerns about doing KMC for long periods because mothers needed rest after delivery. However, the cultural practice of recently delivered women not expected to be doing household chores and availability of other family members were identified as enablers. HH trials provided an opportunity to test the intervention package and showed high acceptability for KMC. Most mothers perceived benefits such as weight gain and increased activity in the infant. Conclusions Community-initiated KMC is acceptable by mothers and adoption rates are high. Formative research is essential for developing a strategy for delivery of an intervention. Trial registration Trial registration number CTRI/2015/10/006267. Name of Registry: Clinical Trials Registry - India. URL of Registry: http://ctri.nic.in/Clinicaltrials/login.php Date of Registration: 15/10/2015. Date of enrolment of the first participant to the trial: 18/04/2015.